Feeding habits of the seahorse Hippocampus patagonicus in San Antonio Bay (Patagonia, Argentina) - Storero, Lorena Pia (2008)
The aim of this study was to evaluate the dietary composition of the Patagonian seahorse Hippocampus patagonicus in San Antonio Bay, Patagonia, Argentina. To this end, analyses of stomach and gut contents were carried out and the diet composition was compared to the potential preys available in the natural environment. Samples were collected from different places in San Antonio Bay, a Marine Protected Area in San Matas Gulf. Type and number of prey present in the digestive tracts were registered and frequency of occurrence (%FO) and number of prey (%N) were calculated for each study area. Amphipods (Gammaridae, Caprellidae and Hiperidae) and decapods are the main dietary items of H. patagonicus in San Antonio Bay. There were differences in %FO and %N at different sites, which could indicate differences in abundance and availability of prey in the environment. No dietary differences were detected between sex and size of seahorse (ANOVA, P>0.05). Results from the present study show that, in nature and probably due to limiting environmental factors, H. patagonicus behaves as an opportunistic predator, which preys on the most abundant and vulnerable species present in the environment.